Correction: Boosting the solar water oxidation performance of a BiVO4 photoanode by crystallographic orientation control. Issue 4 (29th March 2019) - Han, Hyun Soo; Shin, Sun; Kim, Dong Hoe; Park, Ik Jae; Kim, Ju Seong; Huang, Po-Shun; Lee, Jung-Kun; Cho, In Sun; Zheng, Xiaolin
Abstract : Correction for 'Boosting the solar water oxidation performance of a BiVO4 photoanode by crystallographic orientation control' by Hyun Soo Han et al., Energy Environ. Sci., 2018, 11, 1299–1306.